TINJAUAN YURIDIS TERHADAP PENYELESAIAN DAMAI PERKARA SEDERHANA EKONOMI SYARIAH (ANALISIS KASUS DI PENGADILAN AGAMA KEDIRI) - Ahdiyat Ilmawan Nehru; dian berkah (Universitas Muhammadiyah Surabaya, 2020)
ABSTRACTThe objective will be accomplished in the title of the thesis is the author of the above is to find out if the peace process is going on, and the proceedings conducted against a simple matter of Economics Sharia Religious Courts in Kediri were in accordance with the provisions of the law that applies.This research uses the juridical normative approach i.e. researching secondary data or library material, then analyzed qualitative data analysis and results presented with descriptive method, namely by giving a picture in fact regarding the juridical review against a peaceful solution a simple matter of Economics Sharia Religious Courts in Kediri.Based on the results of the research on settlement matters simple economics Sharia Religious Courts in Kediri via the litigation has been in accordance with the provisions of the applicable law, both at the stage of registration, ranging from up to judge drop the verdict. But against the occurrence of the verdict form peacekeeping assignment given by judges in future trials, is not the peace that occurs on the basis of the presence of both parties with the bond Act of peace, but rather the onset of peace because the judge grant the plaintiff's petition to revoke the matter, this occurs after the judge listened to the description of the plaintiff who stated upfront trial that the Defendants had completed his charge to the plaintiff. Besides that the consideration of judge of dikabulkannya petition for annulment of case filed by the Plaintiff because during the trial, the defendants never attend and sent his Deputy, so over the verdict ...Â Keywords : Sharia Economic Disputes, Peace, Trial